Peran Akuntansi dalam Mewujudkan Sustainable Development - Eka Retno Agustin; Trisnawati, Rina (Program Studi Akuntansi - STIE Kesuma Negara Blitar, 2025)
This study examines the role of accounting as measured by green accounting, MFCA, environmental disclosure, environmental performance, and environmental cost towards sustainable development in companies operating in the mining sector and listed on the Indonesia Stock Exchange for the period 2021-2023. The total sample analyzed was 14 companies with 38 data collected. The sample selection technique applied was purposive sampling and the analysis was carried out using multiple linear regression. The tool used for analysis in this study was SPSS version 25. The research findings from the multiple linear regression analysis indicated that green accounting, environmental performance, and environmental cost had no effect on sustainable development. On the other hand, MFCA and environmental disclosure showed an effect on sustainable development. With this study, it emphasizes the importance of companies to obtain social support by adjusting their activities to social values in order to survive in the long term.